PENDAMPINGAN PENGEMBANGAN INSTRUMEN PENILAIAN OTENTIK YANG MENDUKUNG PEMBELAJARAN MENDALAM UNTUK GURU-GURU IPA MTS KABUPATEN TUBAN - Wahyu Budi Sabtiawan; Elok Sudibyo; Hasan Subekti; Dhita Ayu Permata Sari; Aris Rudi Purnomo; Fikky Dian Roqobih; Sapti Puspitarini; Gita Bella Aprilia (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
The current challenge is requiring teachers to be able to implement authentic assessments that support in-depth learning. One of the tools in this implementation is assessment. The problem is that the partner, the MGMP Science Teachers of MTs in Tuban Regency, is not yet accustomed to implementing authentic assessments that support in-depth learning and therefore requires training and mentoring. Based on this, training and mentoring are needed to implement assessments that support in-depth learning. Through this activity, it is hoped that partners can improve their skills in implementing authentic assessments that support in-depth learning. The implementation method is divided into four stages, namely preparation, material presentation, training and mentoring, and evaluation. Participants in this PKM activity were 67 MTs science teachers in Tuban Regency. The results of the mentoring and training showed that (1) there was an increase in the PKM participants' understanding regarding authentic assessments based on pre- and post-test scores; (2) the level of skills of the training participants in planning and implementing authentic assessments was still lacking (thus, more intensive mentoring for participants regarding planning and implementing authentic assessments was needed); and (3) the training participants showed a positive response to the PKM activity.